PROFESSIONAL COMPETENCES AND EXPERIENCE IN SPORTS AND RECREATIONAL AQUATIC FACILITY MANAGEMENT - István BALOGA; Sándor VIZI (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
The present article is aimed to evaluate the current state and suggest new ideas within the management of the aquatic facilities in Romania, as compared to the management in the same industry in the United States of America. Identifying the educational degree of the aquatic facility manager, as well as examining the management activities that can contribute to the improvement of the aquatic facilities performance were the main goals of this study.